Features of Structural Changes in Aluminum Specimens with Various Crystallographic Orientation under Ion Irradiation; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Kryzhevich D. S. Dmitrii; Korchuganov A. V. Aleksandr; Zolnikov K. P. Konstantin; Psakhie S. G. Sergey Grigorievich (2016, 2016)
Title screen